Effects of mechanical insufflation-exsufflation on ventilator-free days in intensive care unit subjects with sputum retention; a randomized clinical trial. - Shota Kubota; Hideki Hashimoto; Yurika Yoshikawa; Kengo Hiwatashi; Takahiro Ono; Masaki Mochizuki; Hiromu Naraba; Hidehiko Nakano; Yuji Takahashi; Tomohiro Sonoo; Kensuke Nakamura (PLoS ONE, 2024)
Background Mechanical insufflation-exsufflation (MI-E) facilitates extubation. However, its potential to reduce the duration of ventilator use remains unclear. Therefore, the present study investigated whether the use of MI-E shortened the duration of mechanical ventilation in patients with high sputum retention. Methods A randomized open-label trial was conducted at a single intensive care unit (ICU) in Japan between November 2017 and June 2019. Ventilated subjects requiring suctioning at least once every hour due to sputum retention were randomly assigned to the MI-E group or conventional care group. The primary endpoint was the number of ventilator-free days on day 28. Secondary endpoints were ventilator days in surviving subjects, the length of ICU stay, and mortality and tracheostomy rates among survivors. Results Forty-eight subjects (81% males) with a median age of 72 years (interquartile range [IQR], 65-85 years) were enrolled. There were 27 subjects in the MI-E group and 21 in the control group. The median number of ventilator-free days was 21 (IQR, 13-24) and 18, respectively (IQR, 0-23) (P = .38). No significant differences were observed in the ICU length of stay (median, 10 days (IQR, 7-12) vs 12 days (IQR, 6-15); P = .31), mortality rate (19% vs 15%; odds ratio [OR], 1.36 [0.28-6.50]; P = .69), or tracheostomy rate among survivors (14% vs 28%; OR, 0.40 [0.08-1.91]; P = .25). Conclusion In ventilated subjects in the ICU with high sputum retention, the use of MI-E did not significantly increase the number of ventilator-free days over that with conventional care.